2008
DOI: 10.1080/08860220701813384
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Hyperbaric Oxygen Therapy in the Treatment of Hemodialysis Patients with Chronic Osteomyelitis

Abstract: Hyperbaric oxygen is effective as an adjunct to aggressive medical and surgical treatment in chronic refractory osteomyelitis among hemodialysis-dependent patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Other proposed mechanisms for its efficacy are inducing angiogenesis, suppressing anaerobic organisms, enhancing antibiotic activity, and promoting oxygendependent osteoclastic resorption of necrotic bone. 73,74 Chen et al 75 and Chen et al 76 have reported on successful treatment of chronic osteomyelitis using hyperbaric oxygen therapy. Skeik et al retrospectively reviewed 118 patients where hyperbaric oxygen was used for different indications.…”
Section: Various Adjunctive Therapies Have Been Used In Patientsmentioning
confidence: 99%
“…Other proposed mechanisms for its efficacy are inducing angiogenesis, suppressing anaerobic organisms, enhancing antibiotic activity, and promoting oxygendependent osteoclastic resorption of necrotic bone. 73,74 Chen et al 75 and Chen et al 76 have reported on successful treatment of chronic osteomyelitis using hyperbaric oxygen therapy. Skeik et al retrospectively reviewed 118 patients where hyperbaric oxygen was used for different indications.…”
Section: Various Adjunctive Therapies Have Been Used In Patientsmentioning
confidence: 99%
“…HBOT works by favoring the action of the inflammatory cells and increases the host response to the targeted pain and swelling. A study conducted in 2008 proved that HBOT has an 80% success rate with a 21-day treatment 39. It can be concluded that HBOT is powerful in conjunction to aggressive medical and surgical treatment 40…”
Section: Uses In Dentistrymentioning
confidence: 99%
“…In clinical nephrology, HBOT was used in cutaneous ulcers due to calciphylaxis, chronic osteomyelitis, hemorrhagic cystitis, and renal zygomycosis [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%